Background Odors Modulate N170 ERP Component and Perception of Emotional Facial Stimuli - Elmeri Syrjänen; Stefan Wiens; Håkan Fischer; Marta Zakrzewska; Andreas Wartel; Maria Larsson; Jonas K. Olofsson (Frontiers in Psychology, 2018)
Successful social interaction relies on the accurate decoding of other peoples’ emotional signals, and their contextual integration. However, little is known about how contextual odors may lead to modulation of cortical processing in response to facial expressions. We investigated how unpleasant and pleasant contextual background odors affected emotion perception and cortical event-related potential (ERP) responses to pictures of faces expressing happy, neutral and disgusted facial expressions. Faces were, regardless of expression, rated more positively in the pleasant odor condition and more negatively in the unpleasant odor condition. Faces were overall rated as more emotionally arousing in the presence of an odor, irrespective of its valence. Contextual odors also interacted with facial expressions, such that happy faces were rated as especially non-arousing in the unpleasant odor condition. The early, face-sensitive N170 ERP component also displayed an interaction effect. Here, disgusted faces were affected by the odor context such that the N170 revealed a relatively larger negativity in the context of a pleasant odor compared with an unpleasant odor. There were no odor effects on the responses to faces in other measured ERP components (P1, VPP, P2, and LPP). These results suggest that odors bias socioemotional perception early stages of the visual processing stream. However, effects may vary across emotional expressions and measurements.